Proceedings of the Twelfth International Congress of Egyptologists: ICE XII, 3rd-8th November 2019, Cairo, Egypt - El-Aguizy, Ola,; Kasparian, Burt, (Bibliothèque générale (Institut français d'archéologie orientale du Caire) ;, 2023)
The 12th International Congress of Egyptologists (ICE) was held in Cairo from the 3rd to the 8th of November, 2019. During the Congress, Egyptologists from 30 countries presented 369 papers covering nine themes: archaeology (current methods and fieldwork); art and architecture; site management, conservation and preservation; history; views on the Egyptian past; language, literature and texts; archaeological science and technology; museums and collections; religious thoughts; society and life in ancient Egypt. This volume presents the Proceedings of ICE XII, which is comprised of 137 contributions encompassing the themes of the Congress that were selected for publication.